2021
DOI: 10.3390/diagnostics11122260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increased Optic Nerve Sheath Diameter on Inadequate Emergence from Anesthesia in Patients Undergoing Robot-Assisted Laparoscopic Prostatectomy: A Prospective Observational Study

Abstract: (1) Background: Robot-assisted laparoscopic prostatectomy (RALP) is preferred over open prostatectomy because it offers superior surgical outcomes and better postoperative recovery. The steep Trendelenburg position and pneumoperitoneum required in Robot-assisted laparoscopic prostatectomy, however, increase intracranial pressure (ICP). The present study aimed to evaluate the effects of elevated ICP on the quality of emergence from anesthesia. (2) Methods: Sixty-seven patients undergoing RALP were enrolled. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Moreover, research on the anesthesiologic management of patients undergoing RALP is limited. Although brain tissue oxygenation seems not to be affected even after three to four hours of steep Trendelenburg positioning [38,39], several studies reported a rise in the ONSD [13,19] and intraocular pressure [40]. We believe that more research is warranted to investigate the effect of steep head-down tilt on brain tissue homeostasis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, research on the anesthesiologic management of patients undergoing RALP is limited. Although brain tissue oxygenation seems not to be affected even after three to four hours of steep Trendelenburg positioning [38,39], several studies reported a rise in the ONSD [13,19] and intraocular pressure [40]. We believe that more research is warranted to investigate the effect of steep head-down tilt on brain tissue homeostasis.…”
Section: Discussionmentioning
confidence: 88%
“…The effect on postoperative cognitive performance in this patient population remains underinvestigated and is therefore not conclusively understood. Patients with a high intraoperative ONSD are more likely to appear disoriented during the awakening period or in the recovery room [19]. Due to the increasing use of RALP (80% of radical prostatectomies in the USA [20]), it is important to better investigate neurological complications and to develop a better monitoring strategy and awareness of potential transient brain damage.…”
Section: Introductionmentioning
confidence: 99%
“…Bang et al [27] enrolled 67 patients Undergoing Robot-Assisted Laparoscopic Prostatectomy, 36 patients had an ONSD increase of 10% or more and only five patients showed increased values of ONSD (>5.7 mm). Significant differences in inadequate emergence were observed only after extubation.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the optic nerve sheath diameter (ONSD) by ultrasound can accurately monitor changes in IOP [41]. A small observational study found that 50% of the patients had an increase of 10% or more in ONSD after pneumoperitoneum and Trendelenburg position were established [42 ▪ ]. However, there were no significant differences in the emergence from anesthesia or neurological deficits between the groups.…”
Section: Central Nervous System Managementmentioning
confidence: 99%